Is there an intermediate-risk non-seminoma? long-term treatment results from a single center - Cvek, Jakub; Feltl, David; Hajek, Jaroslav; Jackaninova, Jana; Ruzickova, Klara; Havranek, Ondrej; Dvorackova, Jana; Dobes, Premysl (Journal of B.U.ON., 2014)
PURPOSE: We retrospectively assessed the treatment results of patients with testicular non-seminoma to evaluate possible predictive and prognostic factors. METHODS: 189 patients with testicular non-seminoma treated between 2000 and 2012 were retrospectively evaluated. Treatment was based on orchiectomy plus chemotherapy (bleomycin/etoposide/cisplatin and vinblastine/ifosfamide/ cisplatin); retroperitoneal lymphadenectomy was only performed for residual disease after chemotherapy. The treatment protocol was updated regularly according to international standards. Overall survival (OS) was evaluated with the Kaplan-Meier method at a significance level of 5% according to stage, Karnofsky performance status (KPS), and chemotherapy dose intensity. RESULTS: OS differed significantly for patients at different TNM stages (p=0.000); however, detailed analysis revealed significantly worse survival only in stage IIIC (10-year OS for IIIC vs IIIA+B, 35 vs 88%, p=0.001), while the difference between IIIB and lower stages was not significant (p=0.383). Patients with no chemotherapy dose reduction had significantly higher OS than those with any kind of dose reduction (10-year OS 96 vs 0%, p=0.000). For stage IIIC disease, however, dose intensity had no influence on OS (p=0.167). KPS had no prognostic significance for OS (KPS<80 vs ≥80, p=0.627) for stage IIIA+B and for stage IIIC. CONCLUSION: The standard of care for testicular non-seminoma offers excellent prognosis with no significant differences in OS for good- and intermediate-risk patients. Reduction of chemotherapy dose negatively impacted OS in patients with stage IIIA+B and thus should be avoided.
Keywords: Neoplasms, Germ Cell and Embryonal; kombinovaná terapie; Humans; Risk; riziko; lidé středního věku; Aged; dospělí; testikulární nádory; senioři; lidé; germinální a embryonální nádory; Adult; Testicular Neoplasms; staging nádorů; Male; Middle Aged; Retrospective Studies; Adolescent; retrospektivní studie; Neoplasm Staging; Combined Modality Therapy; mužské pohlaví; mladiství